THE IMPACT OF SUPPLY CHAIN INTEGRATION DIGITALIZATION AND CIRCULAR PRODUCTION ON OPERATIONAL EFFICIENCY THROUGH GREEN INNOVATION IN INDONESIA’S OIL, GAS, AND ENERGY SECTOR (SECONDARY DATA FROM ANNUAL REPORTS AND SUSTAINABILITY REPORTS, 2020-2024) - Attariq Widy Elhasymi; Yun Yun (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The oil and gas sector is the backbone of national energy, yet it faces challenges in maintaining operational efficiency amidst the pressure of transitioning toward Net Zero Emission (NZE) 2060. This study analyzes the impact of Digital Supply Chain Integration (DSCI) and Circular Production (CP) on Operational Efficiency (OE) with Green Innovation (GI) as a mediating variable. The research focuses on Indonesian oil, gas, and energy companies from 2020 to 2024. The method is quantitative, using path analysis on secondary data from Annual Reports and Sustainability Reports. Results show that Digital Supply Chain Integration has no significant effect on Green Innovation or Operational Efficiency, indicating digital investments are not yet optimized for ecological and cost-efficiency goals. Conversely, Circular Production has a significant negative effect on Operational Efficiency, showing circular practices reduce operational costs through primary input savings. Further, Operational Efficiency has a significant positive effect on Green Innovation. The mediation test confirms that Green Innovation mediates the relationship between Circular Production and Operational Efficiency via eco-design-based innovation. These findings highlight efficiency as an essential foundation for energy companies to achieve sustainable green innovation.